2015
DOI: 10.1103/physrevd.91.084041
|View full text |Cite|
|
Sign up to set email alerts
|

Quantum effects on Lagrangian points and displaced periodic orbits in the Earth-Moon system

Abstract: Recent work in the literature has shown that the one-loop long distance quantum corrections to the Newtonian potential imply tiny but observable effects in the restricted three-body problem of celestial mechanics, i.e., at the Lagrangian libration points of stable equilibrium the planetoid is not exactly at equal distance from the two bodies of large mass, but the Newtonian values of its coordinates are changed by a few millimeters in the Earth-Moon system. First, we assess such a theoretical calculation by ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 75 publications
2
28
0
Order By: Relevance
“…This topic is investigated in Sec. V, where we also show that, among all quantum coefficients κ 1 and κ 2 in the long-distance corrections to the Newtonian potential available in literature [5,[12][13][14][15], the most suitable ones to describe the gravitational interactions involving (at least) three bodies are those connected to the bound-states potential. Finally, conclusions and open problems are discussed in Sec.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…This topic is investigated in Sec. V, where we also show that, among all quantum coefficients κ 1 and κ 2 in the long-distance corrections to the Newtonian potential available in literature [5,[12][13][14][15], the most suitable ones to describe the gravitational interactions involving (at least) three bodies are those connected to the bound-states potential. Finally, conclusions and open problems are discussed in Sec.…”
Section: Introductionsupporting
confidence: 58%
“…Moreover, following Ref. [15], we have the classical values ξ p = 1.87528148802 × 10 8 m and η p = 3.32900165215 × 10 8 m. If we initially set S = 0 in (2.1), we obtain that the perturbative effect of the Sun makes the spacecraft ultimately escape from the stable equilibrium point after about 700 days [52], as is shown in Figs. 1 and 2.…”
Section: Body Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…(3.12), (3.13), and Unfortunately this deviation from the underlying classical theory has no chance to be tested, unlike, for example, the effects some of us predicted in Refs. [10,11,14,15], where it is shown that Earth-Moon Lagrangian points are expected to undergo a displacement of the order of few millimetres from their classical position. Furthermore, we have proved that the result reported in Eq.…”
Section: Concluding Remarks and Open Problemsmentioning
confidence: 99%
“…The collinear libration points L 1 , L 2 , L 3 are unstable, while the triangular libration points L 4 , L 5 are stable for the mass ratio of the primaries less than 0.03852 · · · , [38]. The 3BP, under different forms and aspects, has been used for studies in fundamental physics, general relativity and alternative theories of gravity [1,2,5,10,20,24,31,41].…”
Section: Introductionmentioning
confidence: 98%